External benefits of environmental regulation: resource recovery and the utilisation of effluents - Khalid, A.R.; Wan Mustafa, W.A. (Kluwer Academic Publishers, 1992)
Since 1977, stringent environmental regulation has been progressively imposed on Malaysia's most polluting industry, the palm oil mills. The impact of the regulation on international trade and producer welfare has been quite small compared to the relative benefits to society in terms of changes in the levels of dissolved oxygen in the industrial effluents. External benefits from pollution abatement have been derived. This paper presents a preliminary evaluation of the derived benefits which have a long- term potential of recycling valuable resources while maintaining competitiveness in the international palm oil trade.